Evaluación de la Calidad de la Lana en Ovinos de la Raza Corriedale y Merino en la Región Interandina del Ecuador. - Quinapallo Sarango, Suggeidy Anabel (2019)
This research was carried out in Yanahurco from Saquisilí and in Maca from San José de Poaló, where the wool quality the Corriedale and Merino was evaluated by the Fibrelux equipment by the light diffraction method developed specifically to measure the average diameter of the fibre and using manual techniques wick length measurement, resistance and undulations is performed,32 female sheep, 16 of Corriedale breed and 16 of Merino breed was taken.Wool samples are characterized and compared by applying the quantitative and qualitative descriptive statistics method with the analysis of student’s T variance getting the following results for Corriedale breed, the average of the finesse with a measure of 24,93 ± 0,76 μ, taking into account the lower limit of 22,8μ and an upper limit of 27,06μ wick length, the measure is 84,69 ± 8,32 mm, with a lower and upper limit of 84,69 ± 8,32 mm, and86,82 mm respectively; the Crimpenes or ripples measure is of 4,5 ± 0,45, the lower limit is 2,37and upper is 6,63, there is statistical difference according to value p <0.0001. in the qualitative resustance variable are 15 medium animal and 1 low.Merino sheep finesse with average of 24,04 ± 0,77 μ . With lower limit and upper limit of wick length average of 0,381 ± 2,6 mm, 78,18 - 82,44 mm lower and upper limit and in Crimpness or ripple average is 14,22 ± 0,81 with lower limit 12,09 and upper 16,35 there is statistical difference according to the value p <0,0001. In the qualitative variable there are 7 average high animals 8 middles and one low. In the comparison made of the qualitative variables in the sheep of Ecuador and Australia, , Ecuadorians Corriedale have a mean of finesse of 24,93±0,76 μ with a value p de 0,0139; in the length in Ecuadorian sheep has a measure of 84,69±8,32 mm while the Australians 28,38±1,08 μ the measure is 88±0.15 mm there are numerical differences depending on the value p 0,0003 and in Crimpness or ripples the average for the Ecuadorians is 4,5±0,45 and Australians 3,56±0,27 with numerical difference depending on the value p 0,0838. The Ecudorian Merino sheep compared to the Australians have an average in the finemess of 24,04±0,77μ and Australian there is numerical difference according to the value p 0, 0007, Ecuadorian length wick 80,31±2,6 mm and Austrilians 89,38±6,92 mm with value of p de 0,2352 and Crimpness or ripples 14,22±0,81to the Ecudorian and 8,19±0,49 to the Australian with a statistical difference depending of the value p <0,0001.